(untitled) (XXI Century. Spanish Literature and Culture, 2004)
Coming from the claim that ‘language, above all, is writing’, grammatology is developed: a strategy focalized in a theoretical approximation that will mollify the prejudices of Western thought that undervalue writing. In this study, we see carried out an enormous labor of comparison and approximation of the different ways to highlight individuality which is characteristic of these authors who, interestingly, resemble each other.